Control interno financiero y su incidencia en el presupuesto de la empresa reginabananera S.A. Año 2023 - Moreira Aviles , Joselyn Yulexy (2025)
This research entitled "Internal financial control and its impact on the budget of the company Reginabananera S.A., year 2023" aimed to evaluate the impact of internal financial control on the company's budget compliance. The study applied a mixed approach, using questionnaires based on the COSO model, documentary analysis, and financial and management indicators. A moderate level of confidence in internal control was identified: 56% in the area of accounting and 60% in production, evidencing the need to strengthen the components of monitoring, risk assessment and control activities. As for the budget, 103% of the total planned was fulfilled, with an over-execution of $661,298.00. Actual revenues reached 93% of what was expected and costs increased 13.64% more than budgeted, resulting in an operating loss. In the financial indicators, current liquidity of 0.48 and an acid test of 0.44 were evidenced, reflecting liquidity problems; the indebtedness of the assets was 0.92 and the leverage of 12.57, which indicates high dependence on liabilities. Profitability was affected, with a negative gross margin of -0.01. Regarding management indicators, the company showed efficiency in portfolio turnover of 10.54 times and an average collection period of 34.65 days, while sales turnover 0.45 and fixed asset turnover 0.51 reflected low use of resources. It is concluded that the weaknesses of the internal financial control affected the budget execution, affecting liquidity, profitability and efficiency. It is recommended that the internal control system and budget planning be strengthened.